A preliminary study to evaluate the physicochemical and microbial population dynamics of a blend of pearl millet flour and buttermilk during spontaneous fermentation (Journal of Food and Dietetics Research, 2021)
Objectives: The present study assessed the microbial population dynamics and physicochemical test during the spontaneous fermentation of pearl millet flour and buttermilk blend.Materials and Methods: Pearl millet flour samples were taken from the local market of Rewari and Mahendergarh district of Haryana, whereas buttermilk samples were taken from nearby villages of Mahendergarh, Haryana. pH and total titratable acidity were estimated for physicochemical analysis of the blend sample. Microbiological analysis has been carried out to estimate the microbiological population dynamics of samples using different media i.e., 1) Potato Dextrose Agar; 2) Plate Count Agar; 3) Lactobacillus MRS agar; 4) Eosin Methylene Blue Agar.Results: The subject study mainly deals with the physicochemical test and microbiological analysis of pearl millet, i.e., pH ranges from 3.0 to 6.84 where it was lowest in buttermilk sample at 72 h, and highest is 6.84 in flour sample at 0 h, temperature ranges from 13°C to 31.5°C at different conditions (shaking, refrigeration, room temperature). Total titratable acidity as gm/lactic acid was recorded in the range of 0.4 to 0.96, lowest in the blend sample at 0 h, and highest in the blend at room temperature (72 h). In the samples of the blend the total aerobic count, Lactic acid bacteria count, E. coli count, were up to 7.65 (log cfu/ml), up to 6.8 (log cfu/ml), and 3.48 (log cfu/ml), respectively after fermentation.Conclusion: A preliminary study results suggest that the best storage condition is refrigeration for all the samples. However, on 72 h of fermentation LAB counts were increased. This is only a preliminary study, a study with a large sample and much-organized methods need to be investigated for the outcome of these different conditions of microbial dynamics.
Keywords: Pearl millets; Fermentation; Buttermilk; Lactic acid bacteria; Microbiological analysis